1980
DOI: 10.1111/j.1365-2559.1980.tb02939.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweat‐gland carcinomas: prognosis related to histological type

Abstract: A series of 10 sweat-gland carcinomas is reported. The ages of the patients at presentation ranged from 12 to 79 years. Three of the tumours had shown long latent periods with a mass present for up to 20 years. Prognosis proved to be related to the histological subtype. Thus, two papillary syringocystadeno-carcinomas, one recurring cylindroma, one hybrid cylindroma/adenoid cystic carcinoma and two mucoid carcinomas were apparently all cured by surgery. Two mucoepidermoid carcinomas and one histologically malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 15 publications
2
61
1
Order By: Relevance
“…However, it also revealed an intracystic proliferation of atypical cells without infiltration of the dermis in conformity with lesions previously reported as "syringocystadenocarcinoma papilliferum in situ" (SPCIS) [5,12,13]. There is probably a continuum from a benign SP via various grades of atypia to an infiltrating syringocystadenocarcinoma papilliferum (SPCA), but criteria for grading of these rare tumors have to our knowledge not been determined.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, it also revealed an intracystic proliferation of atypical cells without infiltration of the dermis in conformity with lesions previously reported as "syringocystadenocarcinoma papilliferum in situ" (SPCIS) [5,12,13]. There is probably a continuum from a benign SP via various grades of atypia to an infiltrating syringocystadenocarcinoma papilliferum (SPCA), but criteria for grading of these rare tumors have to our knowledge not been determined.…”
Section: Discussionsupporting
confidence: 83%
“…About 40% are associated with nevus sebaceous in the same area, some of them developing a basal cell carcinoma as well [1]. There are only few reports of transformation of an SP into an infiltrating syringocystadenocarcinoma papilliferum (SPCA) [2][3][4][5][6][7][8][9][10] and even fewer cases showing an SPCA in situ (SPCIS) [4,5,[11][12][13]. The latter tumors are characterized by a disorganized proliferation of atypical cells in the papillary structures of an SP but without tumor infiltration of the surrounding dermis.…”
Section: Introductionmentioning
confidence: 99%
“…The natural history of MCS is variable, with some patients having an indolent course with survival of up to 17 years, while others have an accelerated course with survival of only a few weeks [3, 9]. Cell types showing high-grade undifferentiation and anaplastic changes are associated with an aggressive course, distant metastases and a decreased 5-year survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the English literature revealed nine reports describing 11 cases of MCS with lung metastasis [3, 8, 9, 10, 11, 12, 13, 14]. Data on 12 patients, 6 women and 6 men age 12–79 years at diagnosis of the primary tumor, including the current case, are presented in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cutaneous mucinous carcinoma (MC) is a neoplasm derived from the sweat glands [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25]. Since its first description in 1952, cutaneous MC has been reported to occur on the head [5, 7, 15, 23], neck [6], extremities [11, 13, 17]intertriginous areas [20]and the trunk [1].…”
Section: Introductionmentioning
confidence: 99%